2007
DOI: 10.1128/jcm.01710-06
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Information Systems and Genotyping in Identification of Rotavirus G12 Infections in Residents of an Urban Slum with Subsequent Detection in Hospitalized Children: Emergence of G12 Genotype in South India

Abstract: Rotavirus infections by G12 strains in several countries have recently been described. In this study, we report the emergence of G12 strains in south India. Fourteen cases of G12 infection were identified between June and September 2005. G12 was seen in combination with P[6], P[8], or nontypeable P type. Nine cases, including five symptomatic infections and four asymptomatic infections, were identified as part of routine surveillance for rotavirus infections in a birth cohort in the community between June and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 24 publications
0
42
1
Order By: Relevance
“…Multiple sequence alignment and phylogenetic analysis of the partial VP7 gene sequence of 13 untyped strains identified them as G12 HRV strains, as reported [Ramani et al, 2007]. Further characterization by analysis of the partial nucleotide sequence of all 13 strains (CRI 32215, CRI 32442, CRI 32548, CRI 32608, CRI 32609, CRI 32742, CRI 32920, CRI 33015, RV 404, RV 412, RV 413, RV 417, and RV 430) showed maximum homology with the Indian ISO-5 G12 strain (97-99% at the nucleotide level and 97-99% at the deduced amino acid level).…”
Section: Sequence Analysis Of the Vp7 Encoding Genementioning
confidence: 99%
See 3 more Smart Citations
“…Multiple sequence alignment and phylogenetic analysis of the partial VP7 gene sequence of 13 untyped strains identified them as G12 HRV strains, as reported [Ramani et al, 2007]. Further characterization by analysis of the partial nucleotide sequence of all 13 strains (CRI 32215, CRI 32442, CRI 32548, CRI 32608, CRI 32609, CRI 32742, CRI 32920, CRI 33015, RV 404, RV 412, RV 413, RV 417, and RV 430) showed maximum homology with the Indian ISO-5 G12 strain (97-99% at the nucleotide level and 97-99% at the deduced amino acid level).…”
Section: Sequence Analysis Of the Vp7 Encoding Genementioning
confidence: 99%
“…All G12 strains analyzed in this study clustered in lineage III. P types determined in 12 of the 13 G12 strains from Vellore as reported separately [Ramani et al, 2007], were P[6] in 9 strains (69.2%) and, P[8] in 3 strains (23.1%), with one sample remaining untyped for VP4 (Table I). Since a first round amplification product of the VP4 gene could not be obtained for the untyped sample, sequence analysis was not possible.…”
Section: Sequence Analysis Of the Vp7 Encoding Genementioning
confidence: 99%
See 2 more Smart Citations
“…Use of newly optimised molecular techniques has increased sensitivity of detection and characterisation of unusual rotavirus strains apart from commonly described genotypes [9]. Results of earlier studies in Iran have shown that rotavirus is a major aetiological agent of acute diarrhoea in infants and young children [10].…”
Section: Introductionmentioning
confidence: 99%